Analysis of Heat Gain in Computer Laboratory and Excellent Centre by using CLTD/CLF/SCL Method - Suziyana, Mat Dahan; S. N., Nina; T. M., Yusof; Ahmad Basirul Subha, Alias (Elsevier Ltd, 2013)
Performance of air conditioning system is closely related to heat gain that generated inside the particular room. The amount of heat that generated in the particular room is depend on several factors such as position of the room relative to solar orientation, wall material, electric appliances and number of human occupied in the room. In order to determine heat gain in a room, these parameters have considered and presented in this paper. The method of heat gain determination is using Cooling Load Temperature Differential (CLTD) and Cooling Load Factors (CLF) based on ASHRAE 1997 Fundamental Handbook and then verified by data provided by contractor of building. The case study of the present work is only focused on two rooms specifically Computer Laboratory Room and Excellent Centre Room in Faculty of Mechanical Engineering, University Malaysia Pahang. From this calculation, it has been obtained that the highest heat gain in Computer Laboratory Rom and in Excellent Centre Room is 20458.6 W and 33541.3 W respectively. The assessment of cooling capacity produced by air conditioning system showed that the air conditioning produced over cooling for 23.7 and 25.8 percent for Computer Laboratory and Excellent Centre rooms. Management should reduce the cooling capacity produced by the air conditioning in order to reduce energy consumption.